General sociology: focus on the Philippines - Panopio, Isabel S.; Raymundo, Adelisa A. (Quezon City Philippines, 2004)
General Sociology Focus on the Philippines, the fourth edition is an attempt to infuse new data, issues, and research literatures in sociology with particular focus on the Philippines. The subject matters emphasized are society, culture, social group, and the social interactions taking place with it. The book tries to provide a general scientific orientation on the conceptual scheme of sociology for readers to develop a odological framework for the study of the society. -
Keywords: Sociology